2012
DOI: 10.1002/ajmg.a.35670
|View full text |Cite
|
Sign up to set email alerts
|

Developmental and behavioral characteristics of individuals with Pallister–Killian syndrome

Abstract: Pallister-Killian syndrome is a sporadic disorder caused by the presence of mosaic tetrasomy of the short arms of chromosome 12. Case reports of children with Pallister-Killian syndrome have described a range of developmental and behavioral outcomes, but no systematic studies of these outcomes exist. The objective of this study was to describe developmental and behavioral characteristics of individuals with Pallister-Killian syndrome participating in a national meeting of families and their affected children. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
42
1
2

Year Published

2012
2012
2020
2020

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 28 publications
(47 citation statements)
references
References 18 publications
(20 reference statements)
2
42
1
2
Order By: Relevance
“…No group report24 36 37 42–44 mentions the presence of hexasomic cell lines and these have only been recorded in 313 of 117 individually reported cases (2.6%). This may partly be explained by laboratories not actively seeking further low-level mosaicism once Pallister-Killian syndrome has been diagnosed.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…No group report24 36 37 42–44 mentions the presence of hexasomic cell lines and these have only been recorded in 313 of 117 individually reported cases (2.6%). This may partly be explained by laboratories not actively seeking further low-level mosaicism once Pallister-Killian syndrome has been diagnosed.…”
Section: Discussionmentioning
confidence: 99%
“…A further six reported patients were able to walk and had some speech 1 23–26. One had an IQ of 811 and another of 69 24. One functioned at 24 month level at 6.5 years24 and one was in special needs education at the age of 7 years 25.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…In those studies in which mosaic chromosomal aneuploidy was specifically sought, it was found to be associated with certain phenotypes, including several reports of mosaicism for chromosomal aneuploidy in peripheral blood in children with autism spectrum disorder (ASD). [16][17][18] Given the limitations of using blood to detect aneuploid cells, it is likely that mosaic chromosomal aneuploidy in ASD is not limited to these specific reported individuals but is more prevalent.…”
Section: Introductionmentioning
confidence: 99%